Risk estimation, anxiety, and breast cancer worry in women at risk for breast cancer: A single‐arm trial of personalized risk communication. Issue 11 (2nd September 2019) - Xie, Zhuoer; Wenger, Neil; Stanton, Annette L.; Sepucha, Karen; Kaplan, Celia; Madlensky, Lisa; Elashoff, David; Trent, Jacqueline; Petruse, Antonia; Johansen, Liliana; Layton, Tracy; Naeim, Arash
Abstract: Objective: Elevated anxiety and breast cancer worry can impede mammographic screening and early breast cancer detection. Genetic advances and risk models make personalized breast cancer risk assessment and communication feasible, but it is unknown whether such communication of risk affects anxiety and disease‐specific worry. We studied the effect of a personalized breast cancer screening intervention on risk perception, anxiety, and breast cancer worry. Methods: Women with a normal mammogram but elevated risk for breast cancer ( N = 122) enrolled in the Athena Breast Health risk communication program were surveyed before and after receiving a letter conveying their breast cancer risk and a breast health genetic counselor consultation. We compared breast cancer risk estimation, anxiety, and breast cancer worry before and after risk communication and evaluated the relationship of anxiety and breast cancer worry to risk estimation accuracy. Results: Women substantially overestimated their lifetime breast cancer risk, and risk communication somewhat mitigated this overestimation (49% pre‐intervention, 42% post‐intervention, 13% Gail model risk estimate, P < .001). Both general anxiety and breast cancer worry declined significantly after risk communication in women with high baseline anxiety. Baseline anxiety and breast cancer worry were essentially unrelated to risk estimation accuracy, but risk communication increased alignment of worry with accuracy of risk assessment. Conclusions: Personalized communication about breast cancer risk was associated with modestly improved risk estimation accuracy in women with relatively low anxiety and less anxiety and breast cancer worry in women with higher anxiety. We detected no negative consequences of informing women about elevated breast cancer risk.